Joshua in the Holy Land - Girzone, Joseph F. (New York : Macmillan Pub. Co., 1992)
Joshua, the pious woodcarver, leads his followers to peace in the world as well as the next.
Keywords: Joshua (Fictitious character) -- Fiction; Palestine -- Fiction; Religious fiction; Parables; Religious fiction